2021
DOI: 10.1016/j.ihj.2021.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of echocardiographic left ventricular dyssynchrony with QRS width on surface electrocardiogram in patients with systolic heart failure: An observational study

Abstract: This study aimed to evaluate left ventricular dyssynchrony with QRS width on ECG in patients with systolic heart failure. 100 study patients were classified into two groups. Narrow QRS group-N- QRS (80-119 msec) and Wide QRS group-W- QRS (120-160 msec). Out of each 50 patients in W- QRS group, 38(76%) had LV dyssynchrony and 18 (36%) in N- QRS group had ventricular dyssynchrony. Dyssynchrony in narrow QRS patients with heart failure also needs attention as a therapeutic target in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In biventricular hearts with acquired heart diseases, QRS duration correlates with markers of ventricular dyssynchrony, dilation, and heart failure. 35,36 QRS duration has also been identified as a prognostic indicator in CHD such as tetralogy of Fallot; although, recent studies have shown that its effect may not be independent of LV dysfunction. 37 Similar data in the Fontan population are limited.…”
Section: Discussionmentioning
confidence: 99%
“…In biventricular hearts with acquired heart diseases, QRS duration correlates with markers of ventricular dyssynchrony, dilation, and heart failure. 35,36 QRS duration has also been identified as a prognostic indicator in CHD such as tetralogy of Fallot; although, recent studies have shown that its effect may not be independent of LV dysfunction. 37 Similar data in the Fontan population are limited.…”
Section: Discussionmentioning
confidence: 99%